Trace gases air daily means during Maria S. Merian cruise MSM105 - Sabbaghzadeh, Bita; Glockzin, Michael; Rehder, Gregor (PANGAEA, 2023)
The high surface productivity triggered by nutrient-rich Benguela upwelled waters results in significant enrichment of organic carbon in the sub-surface waters due to enhanced mineralization in the water column and benthic fluxes. Hence, microbial oxygen consuming processes are promoted, driving oxygen depletion that favors trace gases i.e. methane (CH4) and nitrous oxide (N2O) production at relatively shallow depths. During upwelling, gas-rich subsurface waters are also transported towards the surface waters, enhancing trace gas sea-air fluxes. We investigate the variability of these fluxes on seasonal and shorter timescales to understand the intensity of the Benguela upwelling system in gas emissions. The data might serve as a base for projections under a changing climate. The fieldwork took place during the cruise MSM105 (January 11th – February 23rd, 2022) onboard the R/V MARIA S. MERIAN, which encompassed close-coastal and open ocean regions between Mindelo (Cape Verde) and Walvis Bay. The working area of the cruise MSM105 was the Namibian shelf between 18°S and 27°S which are suggested to represent some regional hotspots of trace gas emissions to the atmosphere.The underway mesurement of partial pressures of CH4, N2O, and CO2 in sea surface and atmosphere were determined using IOW's self-built Mobile Equilibrator Sensor System (MESS). The system was described in details elsewhere (Sabbaghzadeh et al., 2021) but in brief, it consists of a custom-built equilibrator (combined shower-head/bubble type) and a control unit lined up with two Los Gatos Research off-axis laser absorption spectroscopy (oa-ICOS) analyzers. In this study, a Model # 908-0011-0001(CO2/CH4/H2O) and a Model # 908-0014-0000 (N2O/CO/H2O) were used. To quantify sea-air gas fluxes, the atmospheric concentration of studied trace gases was measured at several positions during the cruise using a tube with the inlet positioned at front of the bow to minimize ship contamination. All other ancillary parameters out of the MESS system were synchronized with D-ship data with a simultaneous data reduction to one-minute intervals.
Keywords: Benguela Upwelling System; Namibia; Oxygen deficient zones; trace gas; Underway Measurement